Siedlungsgang und ländliche Siedlungsformen im Himalaya-Vorland von Kumaon (Nordindien) - Nitz, Hans-Jürgen (ERDKUNDE, 1968)
The former Indian Himalayan Principality of Kumaon borders Nepal in the north west. Its forested mountain foreland reaches from the foot of the Himalaya 40 km out into the north Indian plain. The natural regions can be divided into a zone of alluvial fans (Bhabar) with porous sandy soils immediately at the montane foot, separated from the well-watered moist-soil Terai by a zone of springs (Fontanili) with humus-rich loam soils. The Terai had already been opened up to peasant farm ing settlement by the time of the Emperor Akbar (c. 1600) but under the Pax Britannica in the 19th century a strong migration from the malarial forest took place to the Ganges plain which was more suitable for settlement. As a result of this desertion process, a high grass savanna spread. This was re-cultivated by new colonists after the Second World War. The following rural settlement forms from the older and youngest settlement phases are found in the Terai today: 1) nucleated villages with mud houses and intermingled block field patterns are the settlement form of the older settlers from the river plain (Figs. 1-3); 2) hamlets with row houses and open-field patterns are the settlement form of the Buxa, a non Indo-Aryan tribe long settled in the Terai (Figs. 4, 5); 3) the State colonisation agency laid out regular colonists villages, with standardised house types and compact holdings in a chequerboard pattern. Refugees from West Punjab, East Bengal, ex-servicemen and political sufferers were settled on these (Figs. 3, 6); 4) the new settlers from Bengal often built isolated farmsteads in traditional style on their holdings outside the villages (Fig. 7); 5) finally, after the end of the War, a large number of latifundia with bungalows and workers settlements were founded on the lands of deserted villages. Up to the end of the 19th century the Bhabar, unsuit able for conventional agriculture because of its dry soils, was only settled temporarily in winter by mountain peasants, who came to the warm foreland to avoid the cold montane winter. In the second half of the 19th century, British engineers built a cemented network of canals fed by the small rivers emerging at the mountain edge. The land thus irrigated was divided up into regular strip-type landholdings of 3-4 ha and given to settlers from the mountains. Row villages determine the settlement picture of the Bhabar. The dominant type of colonists farmstead is shown in Fig. 8. Even today, peasants from the mountains build temporary winter huts in the Bhabar (Photo 1) and hire themselves out for the sugar cane harvest or for lumbering in the forests. All-year-round cattle stations (khattas) are maintained on behalf of Bhabar villages in the forests of the zone of springs (Photo 2). Temporary khattas are set up in winter by transhumant herdsmen from the mountains and in summer by nomadic shepherds with buffalo herds from the Ganges depression. Fig. 9 gives a comprehensive view of the spatial pattern of rural settlement forms in the Himalaya Foreland of Kumaon.